Model Pendampingan Empatik dalam PAK: Kajian Konseling Yesus di Yohanes 4 untuk Peserta Didik Era Gen Z - Deo D. A. Pangestu; Yosep H. E. Baruno (Nubuat : Jurnal Pendidikan Agama Kristen dan Katolik, 2026)
Students in the Generation Z era face increasingly severe psychosocial challenges due to the rapid development of digital technology and the moral degradation that follows. National survey data shows that one in three Indonesian teenagers has a mental health problem, while most Christian Gen Z do not have a spiritual mentor and feel distressed by worries about the future. In the midst of this reality, the PAK approach, which is still dominated by doctrinal knowledge transfer, is considered not able to accompany students comprehensively. This study aims to analyze Jesus' empathetic counseling approach in John 4:1-42 in an integrative manner, bringing together the perspectives of biblical theology and Rogers counseling psychology, in order to formulate a contextual and applicable mentoring model for PAK teachers. The method used is a literature study with a combination of thematic analysis and contextual biblical hermeneutic analysis. The results of the study show three main findings. First, Jesus' approach in John 4 is shown to be in harmony with Rogers' three conditions of effective counseling, empathy, unconditional acceptance, and congruence, forming a paradigm of companionship that is relevant throughout the ages. Second, Jesus' companionship principles have proven to be relevant to Gen Z's five key psychosocial needs, including unconditional acceptance, full presence, non-judgmental confrontation, transformative mentoring, and space to truly be heard. Third, this study formulates the Empathic Integrative Accompaniment Model (EIAM) as an original contribution that has never been formulated before in the academic literature of PAK Indonesia, consisting of five steps: full presence, empathy-based active listening, unconditional acceptance, empathic confrontation, and transformative mentoring. This model offers flexible guidance for PAK teachers to guide, explore potential, and accompany learners to become agents of change in their communities, while affirming the pedagogical relevance of biblical texts to today's educational challenges.